Optimization of Reception Dwell Time through Lean Manufacturing: A Case Study in a Logistics SME in Peru - Herrera-Abt, Percy Renato; López-Malvaseda, Marco Antonio; Quiroz-Flores, Juan Carlos (LACCEI, 2025)
The logistics industry faces significant challenges in managing product dwell time in warehouse reception areas. Delays in receiving and processing goods lead to inefficiencies and reduced productivity. Previous studies have demonstrated the benefits of Lean Manufacturing tools like 5S and Standardized Work in various sectors, but there remains a gap in their application to logistics reception areas. This research addresses these issues by proposing a model to reduce product dwell time. The main challenges include prolonged product separation, errors in pallet placement, and inaccurate data entry. These inefficiencies necessitate the urgent application of Lean tools to streamline processes and improve workflow. The study's key findings show a 50% reduction in dwell time, a significant boost in productivity, and a reduction in operational errors. These improvements validate the proposed model in real-world logistics setting. This research contributes to the literature by adapting Lean tools to logistics, with measurable results in cost reduction and increased operational efficiency, offering a foundation for further research in similar contexts.